Development and Extension of Agricultural Production Technology - Vallaeys, Guy; Silvestre, Pierre; Blackie, Malcom J.; Delgado, Christopher L. (International Food Policy Research Institute, 1987)
The discussion in the previous chapters makes it clear that the environment for technological change in agriculture is highly variable across ecological regions and policy systems and is frequently exceedingly complex. Generally, the problems of technological change are especially intractable in the semiarid areas but also are acute in the lowland humid tropics. Research to date has perhaps been most successful in the high-potential areas of the high-altitude plateaus and irrigated zones, which account for a very small percentage of total cropped area in the region. Yet even here, major problems remain on the institutional side to insure a steady flow of appropriate innovations to a dynamic agriculture.